Introduction to computers for healthcare professionals - Joos, Irene; Nelson, Ramona; Smith, Marjorie J. (Sudbury, Mass. : Jones and Bartlett, 2010)
An introductory computer literacy text for nurses and other healthcare students, Introduction to Computers for Healthcare Professionals explains hardware, popular software programs, operating systems, and computer assisted communication. The Fifth Edition of this best-selling text has been revised and now includes content on: Online storage; Communication and online learning including info on PDA's, iPhones, IM, and other media formats; Operating systems including vista; Distance learning including video conferencing and streaming video.
On the way to computer and information literacy -- Computer systems : hardware, software, and connectivity -- The computer and its operating system environment -- Software applications : common tasks -- Introduction to word processing -- Introduction to presentation graphics -- Introduction to spreadsheets -- Introduction to databases -- Using the world wide web -- Computer-assisted communication -- Distance education : a student perspective -- Information : access, evaluation, and use -- Privacy, confidentiality, security, and integrity of electronic data -- Healthcare informatics and information systems.
Revised edition of: Introduction to computers for healthcare professionals / Irene Joos [and others]. 4th ed. c2006.
Includes bibliographical references and index.
Keywords: MEDICINE -- DATA PROCESSING; NURSING -- DATA PROCESSING; MEDICAL INFORMATICS; NURSING INFORMATICS; COMPUTER LITERACY; COMPUTERS; ELECTRONIC DIGITAL COMPUTERS; COMPUTER PROGRAMS; COMPUTER SOFTWARE